Synthesis and Characterization of Dispersible Geopolymer Nanoaggregates - Medpelli, Dinesh; Seo, Dong-Kyun (Frontiers in Chemistry, 2022)
We present a simple synthetic route to submicron-sized both potassium- and sodium-based geopolymer nanoaggregates whose nanostructure is suitable for applications in polymer composites. The new synthetic method is based on the chemical mechanism of geopolymer formation in which the extent of cross-liking of geopolymer primary particles is dependent of the alkali concentration and the relative amount of water in the precursor mixture. The products exhibited ~50 – 60 nm-sized primary particles along with ~15 – 20 nm-sized smaller particles. The external surface areas of the products were high, up to 231 m2/g, especially for the sodium-based geopolymer. The primary particles are fused together to form aciniform nanoaggregates with average size of about 400 nm and mesopore volume up to about 0.59 cm3/g. The zeta potential of the nanoaggregates was below ‒ 40 mV in the pH range of 5.7 ‒ 12, demonstrating that the particles are stable in this pH region and do not undergo aggregation and/or agglomeration. All these characteristics make the new material favorable in application of the material in nanofiller application.